The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pone.0189004
|View full text |Cite|
|
Sign up to set email alerts
|

Caveolin-3 promotes glycometabolism, growth and proliferation in muscle cells

Abstract: ObjectiveCaveolin-3 (CAV3) protein is known to be expressed specifically in various myocytes, but its physiological function remains unclear. CAV3, located at the cell membrane, may promote the sensitivity of the Akt signaling pathway, which is closely related to glucose metabolism and to cell growth and proliferation.MethodsThe CAV3 gene was stably transfected into C2C12 muscle cells, and the effects were evaluated by biochemical assays, WB and confocal microscopy for the observation of cellular glucose metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The Caveolin-3 also interacts with phosphofructokinase-M (PFK-M), a key enzyme in the control of glycolysis in a glucose dependent manner, and may play a role in the regulation of energy metabolism in skeletal muscle fibers [ 90 ]. Shang et al [ 91 ] have shown that in skeletal muscle cell line C2C12, Cav3 protein can activate Akt signaling and increase glucose transporter type 4 (GLUT4) localization at the cell surface, leading to increased glucose uptake. This in turn promotes myocytes’ growth and proliferation.…”
Section: Role Of Caveolin-3 In Energy Metabolismmentioning
confidence: 99%
“…The Caveolin-3 also interacts with phosphofructokinase-M (PFK-M), a key enzyme in the control of glycolysis in a glucose dependent manner, and may play a role in the regulation of energy metabolism in skeletal muscle fibers [ 90 ]. Shang et al [ 91 ] have shown that in skeletal muscle cell line C2C12, Cav3 protein can activate Akt signaling and increase glucose transporter type 4 (GLUT4) localization at the cell surface, leading to increased glucose uptake. This in turn promotes myocytes’ growth and proliferation.…”
Section: Role Of Caveolin-3 In Energy Metabolismmentioning
confidence: 99%
“…The K15N mutation reduces the CAV3 protein on the muscle cell membranes by ~95% (32). This reduction causes the abnormal localization of proto-oncogene tyrosine-protein kinase Src on the Golgi (33) and leads to CAV3 protein retention (15). Consistent with these data, western blot analysis performed in the current study indicated that the CAV3 K15N mutation led to decreased recombinant CAV3 protein expression in muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, IR and GLUT-4 are associated with glucose metabolism and are localized to membrane caveolae, with their expression being regulated by CAV3 on the cell membrane. CAV3 can enhance the expression of IR (3840) by stimulating IR kinase activity, increasing the stability of IR at the sarcolemmal membrane and reducing its degradation (12), stimulating the phosphorylation of IRS-1 and activating the PI3K/AKT signaling pathway (15,18). Activated AKT not only promoted the translocation of GLUT-4 to the plasma membrane and enhanced glucose uptake, but also induced the phosphorylation of GSK3β, which leads to glycogen synthesis via the activation of glycogen synthase (41,42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of dominant-negative cav3 leads to decreased glucose uptake and glycogen synthesis in C2C12 cells, which is attributed to decreased Akt phosphorylation (4345). Conversely, an increase in wildtype cav3 expression is sufficient to enhance Akt phosphorylation and glucose uptake (46). Indeed, LPCAT3 knockdown substantially increased cav3 content in C2C12 myotubes (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%